Donor/recipient ascending aortic diameter ratio as a novel potential metric for donor selection and improved clinical outcomes in heart transplantation: a propensity score-matched study - Masroor, Matiullah; Chen, Yuqi; Wang, Yixuan; Dong, Nianguo (Frontiers in Cardiovascular Medicine, 2023)
Background: Donor/recipient size matching is of utmost clinical importance in heart transplantation. Size matching is usually done by body weight, height, body mass index, body surface area, and predicted heart mass ratios. Precise size matching is important to achieve better clinical outcomes. This study aims to determine donor/recipient ascending aortic diameter (AAoD) ratio as a metric for donor selection and its effect on postoperative clinical outcomes in heart transplant patients.We retrospectively reviewed all consecutive patients who underwent heart transplantation from January 2015 to December 2018. A cutoff value for donor/recipient AAoD ratio (which was an independent variable for the primary endpoint during unmatched cohort analysis) was determined for predicting in-hospital death. A propensity score-matched (PSM) study was performed and a Cox regression model was created to identify independent preoperative predictors of in-hospital mortality. The primary end-point was all-cause in-hospital mortality.Results: A total of 361 patients underwent heart transplantation during the given period. A cutoff value for donor/recipient AAoD ratio of 0.8032 was determined for predicting in-hospital death. The patients were divided into two groups. Group A, AAoD < 0.8032 (n=96), and Group B, AAoD > 0.8032 (n=265). PSM was performed to equalize two groups each 77 patients in terms of risk. After PSM, on multivariate analysis independent predictors of in-hospital mortality were donor/recipient PHM ratio (HR 16.907, 95% CI 1.535-186.246, P=0.021), donor/recipient AAoD ratio < 0.8032 (HR 5.398, 95% CI 1.181-24.681, P=0.030), and diabetes (HR3.138, 95% CI 1.017-9.689, P=0.047). Group A had higher 3-year mortality than Group B (P=0.022). The surgery time, postoperative RBC, plasma, and platelets transfusion were higher in group A (P<0.05). The use of continuous renal replacement therapy (P=0.054), ECMO (P=0.086), and ventilation time (P=0.079) was relatively higher in group A.The donor/recipient AAoD ratio is a potential metric for postoperative outcomes and patient matching in heart transplantation. A donor/recipient AAoD ratio > 0.8032 could improve post-heart transplantation outcomes and donor heart utilization.